Community and union-led Living Wage campaigns. Issue 6 (2nd October 2017) - Prowse, Peter; Lopes, Ana; Fells, Ray
Abstract : Purpose: The purpose of this paper is to demonstrate different approaches to effective campaigning in support of the Living Wage and so this paper contributes to the broader debate over the nature of the union movement's engagement with community groups in pursuit of workplace and social issues. Design/methodology/approach: The paper presents a systematic comparison of a union-led and a community-led campaign, drawing primarily upon interview and survey data. Findings: Though different, both campaigns met with a measure of success in improving employee pay and in increasing union membership suggesting a pragmatic approach to the building of union-community relationships. Practical implications: The paper shows the need for campaigners to adopt a strategic approach in identifying the target for their campaign, and also the importance of shaping a persuasive argument. Originality/value: The paper reaffirms the importance of traditional union-led campaigning alongside campaigning through engagement with community groups and so offers a broader framework for exploring the relationships between union and community groups.